Relatório de Estágio Profissional "O Desafio de Aprender a Ensinar" - Alexandre Oliveira Santos (2017)
The following document intends to reflect on the experiences lived in practicum training conducted in a middle and high school based in the city of Espinho. The practicum training is an integral part of the Master's Degree in Teaching of Physical Education in Primary and Secondary Education. This report also analyses the student teaching practicum, specifically the tasks and activities developed throughout the year. It contains the entire journey associated with the practicum training, including the difficulties, the strategies and the new learning's that were faced, developed and obtained. The practicum was conducted along with two other student teachers and supervised by a cooperating teacher, from school and a supervisor from the faculty. This document entrails five main chapters: I - Introduction, which goes over the formal structure of the practicum report and its relevance to the learning process; II - Personal Dimension, covering my personal traits and the choices that lead me to this career path; III - Professional Practice Framework, related to the legal and institutional framework of the practicum training, the school as a social institution and the classes taught; IV - The Undertaking of the practicum training, divided into three areas: 1. Organizing and Managing of Teaching and Learning (teaching concepts, planning processes and evaluations); 2. School Participation and Relationship with the Community (School Sports, form tutor duties and Other Activities); 3 - Professional Development, presenting a study named as "Functional Training in the context of Physical Education classes: a Study in a High School Class"; And the final chapter, V - Conclusions and Prospects for the Future, an examination of the mental and emotional processes of the internship and potential outcomes for the future.